Autophagy and proteasome interconnect to coordinate cross‐presentation through MHC class I pathway in B cells. Issue 10 (19th July 2016) - Dasari, Vijayendra; Rehan, Sweera; Tey, Siok‐Keen; Smyth, Mark J; Smith, Corey; Khanna, Rajiv
Abstract : Cross‐presentation of exogenous protein antigens by B cells through the major histocompatibility complex (MHC) class I pathway in lymphoid malignancies, and transplant setting has been recognised as an important mediator of immune pathogenesis and T cell‐mediated immune regulation. However, the precise mechanism of cross‐presentation of exogenous antigens in B cells has remained unresolved. Here we have delineated a novel pathway for cross‐presentation in B cells, which involves synergistic cooperation of the proteasome and autophagy. After endocytosis, protein antigen is processed through an autophagy‐ and proteasome‐dependent pathway and CD8 + T‐cell epitopes are loaded onto MHC class I molecules within the autophagolysomal compartment rather than the conventional secretory pathway, which requires transporters associated with antigen processing‐dependent transport. Interestingly, this cross‐presentation was critically dependent on valosin‐containing protein (VCP)/p97 ATPase through its participation in autophagy. Loss of VCP/p97 ATPase was coincident with accumulation of LC3‐II and marked reduction in antigen presentation. These observations provide unique insight on how the autophagy and proteasomal degradation systems interconnect to coordinate MHC class I‐restricted cross‐presentation in B cells.